Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Chen, Ming-Zhu; Wang, Jun-Feng; Ouyang, Jian-Ping; Deng, Yi-Rong; Yang, Mei-Ting; Xun, Yu-Dian; Shi, Xiao-Hui; Tang, Guang-Yong; Mo, Jian-Ying; Ye, Han-Jie; Li, Qu-Sheng (Journal of hazardous materials, 2025)
Elevated levels of dissolved organic matter (DOM) and sulfate resulting from urban anthropogenic activities can enhance microbial mobilization of arsenic (As) in contaminated environments. However, the microbial assembly mechanisms governing DOM- and sulfate-driven As biotransformation remain poorly understood. In this study, anaerobic microcosm incubations were conducted to simulate the effects of varying DOM and sulfate concentrations on As speciation, microbial functional communities, keystone taxa, and community assembly processes in shallow aquifers of lateritic red soil regions contaminated with As. The results revealed that increased DOM or sulfate loading significantly elevated dissolved As(III) concentrations, reaching up to 6.00 mg L⁻¹ and 3.24 mg L⁻¹ , respectively, followed by partial re-immobilization through the formation of Fe–As–S minerals such as FeAs₂ and FeAsS. Ten dominant genera capable of reducing As(V), SO₄²⁻, or Fe(III) were identified across both DOM and sulfate treatments, including Citrobacter, Desulfosporosinus, and Clostridium. Most keystone taxa also demonstrated these metabolic capabilities. Analysis of community assembly mechanisms indicated that the arsenate-reducing genus Citrobacter (33.13–55.18 %) was enriched under deterministic selection. In contrast, Desulfosporosinus (2.47–10.03 %) became dominant under sulfate amendment via homogeneous selection, while iron-reducing genera such as Clostridium (4.29–24.05 %), Enterococcus (7.77–13.44 %), and Bacillus (1.63–5.45 %) were primarily governed by stochastic processes. Overall, arsenate-reducers were assembled deterministically, whereas iron-reducers were assembled stochastically. These findings provide mechanistic insights into the microbial mediation of As mobility and support improved risk assessment of As contamination in shallow aquifer systems. [Display omitted] •Dissolved organic matter and sulfate significantly enhance As release from sediments.•Arsenic transformation is driven by arsenate-, iron-, and sulfate-reducing bacteria.•Assembly of arsenate-, sulfate-reducing bacteria are driven by deterministic factors.•Assembly of iron-reducing bacteria is dominated by stochastic processes.